Study on the Failure Characteristics of Coal Wall Spalling in Thick Coal Seam with Gangue - Guosheng Li; Zhenhua Li; Feng Du; Zhengzheng Cao (Advances in Civil Engineering)
Coal wall spalling is one of the main factors restricting the safe and efficient mining of thick coal seam, and the gangue has an important impact on the coal wall spalling. To obtain the failure characteristics of coal wall spalling in thick coal seam containing gangue, numerical calculation and theoretical research were used to analyze the morphological differences of coal wall spalling with different gangue positions. Besides, the damage depth, width, and stress environment of coal wall panel caused by the position of gangue were mainly studied, and the failure mechanics model of coal seam containing gangue was established by using the stability theory of pressure bar. The results show that, compared with coal wall spalling in coal seam without gangue, coal seam with the lower and middle gangue has a significant weakening effect on the wall spalling, and coal seam with the upper gangue has little effect on the wall spalling. In the case of coal seam with gangue, the upper gangue has the highest risk area of coal wall spalling with the maximum depth and width of 2.0 m and 2.3 m. For coal seam with the upper gangue, the dangerous areas of coal wall spalling are mainly distributed in the vicinity of the gangue; for coal seam without the gangue, they are mainly distributed in the middle of the coal seam. The gangue cannot change the law of the external stress distribution of the coal seam, but it has an obvious impact on the internal stress distribution of the coal seam. With the different positions of the gangue, the stress distribution in the coal seam has a great difference, and the maximum difference is 1.8 MPa. This shows that the stress environment of the coal seam containing gangue has the following typical characteristics: “the external stress is controlled by the overburden fracture, and the internal stress environment is controlled by the gangue.” Through the mechanical analysis of the coal seam containing gangue, it is further verified that the coal seam containing gangue is more prone to spalling at the position of gangue.